Anatomical and Clinical Study of Liver Steatosis Severity as a Predictor of Sudden Unexpected Death in Metabolic Syndrome - Khilji, Abdullah; Rajesh, Rajesh; Rukhsar, Hina; Shaikh, Muhammad Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Metabolic syndrome is a disorder that impacts on several organ systems and liver steatosis has risen as a possible marker of more profound metabolic damage. Knowledge on whether the severity of steatosis is a predictor of sudden unexpected death could help to elucidate the relationship between the liver and the heart in a case of advanced metabolic disease. The paper has analyzed the clinical and anatomical value of steatosis severity in postmortem cases, whose findings can be used in preventive medicine and in autopsies. Methodology: The analytical clinico-anatomy research was carried out between January 2022 and January 2023 in Khairpur Medical College, Khairpur Mir’s. Eighty two consecutive cases of medico-legal autopsies that met diagnostic criteria of metabolic syndrome were included. Demographic data, microscopic liver and cardiac, and comprehensive histopathological were noted. They were statistically compared, correlated and odds ratios to determine the relationship between the severity of steatosis and sudden unexpected death. Results: Severe steatosis was much more prevalent with sudden death cases and was characterized by increased grades of inflammation, advanced stages of fibrosis, and increased chances of steatohepatitis. The same pattern was observed in cardiac abnormalities which included increased heart weight, left ventricular hypertrophy and myocardial fibrosis where there was a close association with the severity of hepatic injury. Severe steatosis was a predictive factor of sudden unexpected death (p < 0.001), and there was also evidence that showed that liver pathology and cardiac remodelling were connected through a common metabolic pathway. Conclusion: The severity of liver steatosis is a valuable anatomical predictor of people with metabolic syndrome that could be prone to sudden unexpected death. These results underscore the importance of steatosis assessment in clinical prevention and forensic studies in which early detection of severe hepatic involvement can be used to emphasize individuals with high risk.